AGREGASI TROMBOSIT DAN MEAN PLATELET VOLUME DENGAN SINDROM METABOLIK TERKAIT KEGEMUKAN - Nindia Sugih Arto; Adi Koesoema Aman; Dharma Lindarto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
The hyperactivity of platelet had been seen in patients with metabolic syndrome which can be caused by several factors, such as:insulin resistance, obesity, dyslipidemia and hypertension. The hyperactivity of platelet leads to its aggregation that can be increased therisk of cardiovascular disease. This study is aimed to know the platelet aggregation and mean platelet volume in patients with metabolicsyndrome and obesity by determination 30 patients were choosen for this cross sectional study, those whom attended to the laboratoryand policlinic at H. Adam Malik Medan Hospital, between May 2013 until August 2013. The diagnosis used of metabolic syndromecriteria established by the International Diabetic Federation 2005. From the 30 patients with 15 metabolic syndrome and 15 obesity,four patients were excluded because of their tryglyceride were more than 200 mg/dL. There is no significant differences between theplatelet aggregation with the agonist adenosin difosfat (ADP) in patient with metabolic syndrome and obesity. And there is no significantdifferences of the mean platelet volume values between the metabolic syndrome (9.6±0.93) and the obesity group (9.73±0.74), with pvalue 0.846. Based on this study there is no significant differences between the platelet aggregation and the Mean Platelet Volume values(MPV) in the metabolic syndrome and the obese group